What animals teach us about politics - Massumi, Brian (Duke University Press, 2014)
In this concise book, the noted theorist Brian Massumi takes up the question of "the animal." Treating the human as animal, he develops a concept of an animal politics, which he uses as the basis of an expanded notion of the political.